Telematic Art: The Italian Case. PostMachina, MIDⱯ, and Tempo Reale before and after the 42nd Venice Biennale (Connessioni remote. Artivismo_Teatro_Tecnologia, 2025)
The Italian case of Telematic Art remains underdocumented in specialized studies. The experiences of the artist collectives PostMachina, MIDⱯ, and Tempo Reale, founded in Bologna, Milan, and Calcata (Viterbo) between 1983 and 1986, are largely absent from international literature and have received limited scholarly attention even in Italy. Drawing on archival materials, this study examines their experimental practices, tracing their distinct artistic languages, their connections with key figures in the contemporary art scene, the critical engagement of art critics such as Maria Grazia Mattei, and their institutional partnerships: cultural, from the Centre Pompidou to Ars Electronica; corporate, from RAI to Italcable; and political, with major European institutions of the time. While PostMachina emphasized the role of human intervention within technological processes, MIDⱯ developed an ideographic neolanguage for the telematic age, and Tempo Reale engaged with themes of peace, female solidarity, and the inclusion of communities marginalised from global networks. These investigations, both preceding and following the peak of institutional recognition for Telematic Art at the 42nd Venice Biennale, delineate a dimension of Italian aesthetic practice—intrinsically and ideally transcultural—warranting a critical repositioning within the broader phenomenology of communication art.
Keywords: Telematic Art; Ubiqua; PostMachina; MIDⱯ; Tempo Reale